(untitled) (International Journal of Engineering and Computer Science, 2014)
An ad hoc network is a collection of mobile nodes which communicate with each other using multi-hop wireless links. MANET nodes are equipped with wireless transmitters and receivers. In these networks, nodes act as router as well as host enabling the cooperation between them. In this paper we focus on the impact of mobility models (Random Waypoint and Group Mobility Model ) and Energy Models (Mica Motes, Micaz, Generic ) on the performance of reactive routing protocols AODV, DSR, DYMO, and LAR. With the help of Qualnet 5.2 simulator, we investigated various scenarios by varying number of nodes, maximum velocity of the mobile nodes, Pause time and Packet size. Performance analysis is carried out on the basis of Throughput, Packet delivery ratio, Jitter, End to End Delay, Total Energy Consumption under mobility and Energy model.this work shows that mobility models and energy models have great effect on the performance of routing protocols.